Mana māna : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters of Māori Visual Arts at Massey University, Palmerston North, New Zealand - Ireland, Kim Marie (Massey University, 2024)
This exhibition report, Mana Māna, reflects a four-year journey of artistic exploration and research into uku as a medium for understanding both my identity and my transgender tama. We take a deep dive into the rangahau of mana wāhine theory to understand the oppression of wāhine and our cosmogony. The overlap of takatāpui and Māori rainbow within mana wāhine provides a solid foundation for why it is the platform for fighting discrimination. Pūrākau, as a methodology is rationalised for its capacity to embed cultural codes, transmit mātauranga, and is utilised as a wellbeing approach by Māori clinicians. Takatāpui participant, Hariata Wilson, recalls their story of healing through the experience of mana atua wānanga. Woven throughout the report are Papatūānuku, Hineahuone, Hinehauone, Hinetītama, Hinenuitepō and Hinepūtehue. Each appearance is a reminder of their significance to this kaupapa. Thinking is sculpted and marked into the uku, with the guidance of three toi māori practitioners, Reuban Paterson, Colleen Waata Urlich and Paerau Corneal. Key challenges and aha! moments are disclosed as turning points in both the making of the hue and the installation; Māori Marsden’s philosophy moves the space into Te Pō. Finally, as this journey comes to an end, I look to me and my son, and I perceive an arrival.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts); 440506 Sexualities